Konseling Menggunakan Buku Saku "Gentas" dan Pemberian Minyak Kelapa Murni terhadap Pengetahuan Gizi, Asupan Zat Gizi dan Status Gizi Anak Sekolah Dasar yang Obesitas di Kota Kendari: Penelitian Kuasi Eksperimen - Rosnah, Rosnah; Petrus, Petrus; Fathurrahman, Teguh; Gobel, Sri Yunanci V; Masrif, Masrif; Misbah, Sitti Rachmi; Atoy, Lena (Health Information : Jurnal Penelitian, 2022)
Obesity in children can continue into adulthood accompanied by the risk of comorbidities such as coronary heart disease, stroke, gallbladder disease, diabetes, hypertension, hyperlipidemia, and various other diseases that can reduce life expectancy. Nutrition education or assistance through counseling is one of the efforts to prevent nutrition and health problems, because it can increase knowledge and change behavior to achieve optimal nutritional and health status. There are various factors that cause obesity, including excessive food intake, lack of physical activity, genetic, hormonal, and environmental factors. Virgin coconut oil (VCO) contains 70-85% medium chain fatty acids (MCFAs) which are easily oxidized and are not stored in body fat tissue (adipose), provide a feeling of fullness, and help reduce appetite. With a reduced appetite, the calorie intake from food can also be reduced, thus allowing for weight loss. The purpose of this study was to determine the effect of counseling using pocket books and giving VCO on nutritional knowledge, nutrient intake and nutritional status of obese elementary school students at Madrasah Ibtidaiyah (MI) Ummushabri Pesri Kendari, in March-August 2018. This type of research was a quasi-experimental design. pre test and post test. The population in this study were all obese elementary school students in grades 4, 5, and 6 aged 10-12 years. A sample of 30 people was taken by purposive sampling. Data analysis was performed using paired T-test. The results showed that there were significant differences in knowledge of nutrition, energy intake, protein, and carbohydrates in research subjects after nutrition counseling was carried out using the "Gentas" pocket book and VCO administration. Meanwhile, in the intake of fat, fiber and nutritional status, there was no significant difference after the intervention.